TYPOLOGY AND CONDITIONS FOR THE APPLICATION OF ANTI-CRISIS STRATEGIES - Anna A. Chernova (Статистика и экономика, 2016)
The article analyzes the essence andforms of the anti-crisis strategy, which is the basis for the development of anti-crisisprograms. The study formulated factors, allowing most effectively to use speciﬁc types of strategies in the conditions ofcrisis.